Effect of ZnO nano inclusion on ZnO-PCL nanocomposites evolution on its dielectric properties - Yakubu, Abubakar; Abbas, Zulkifly; Ahmad, Ahmad Fahad; Mohammed, Keiser (2015)
This study involves an investigation to ascertain the effect of ZnO nano inclusion on the evolution and dielectric properties of ZnO-PCL nanocomposites. The effect of the nano inclusion towards attenuation of the composites is also reported. In this study, ZnO nano particles and polycaprolactone (PCL) were blended to form composites using melt blending technique. The composites were employed to study the effect of nano inclusion on the materials. Further analysis were achieved using XRD to investigate the phases of the composites and the crystallite size using Scherrer equation, SEM and EDX for the morphology and elemental composition of samples. The XRD spectra indicated that the ZnO nano particle reacted well during melt blending. Amongst other findings, it was confirmed that the dielectric constant increases as the ZnO nano content increases. The high dielectric properties of the composites makes it suitable for small microwave absorption devices.